Some empirical observations on the correlates of quackery propensity in Sindh’s populace - Khan, Rehan (Journal of the Pakistan Medical Association, 2023)
The current research provides an insight into what are the factors that influence people in Sindh to seek medical treatment from a quack. For this purpose an observational qualitative study was carried out between December 1, 2020 and June 30, 2022. The study used a purposive sampling technique, and the sample size was measured using data from anti-quackery campaigns run in 29 Sindh districts. To identify and collect data on quacks, a quackery-regulatory-intervention-induced questionnaire was used. The public’s propensity for quacks is due to a number of factors, including: (1) simple and compounding ignorance among those seeking medical care; (2) quacks are more persuasive than doctors, (3) low doctor-to-patient ratios result in less interaction between the two, which dissatisfies the patients; —Continue